Phase Transition, Magnetocaloric Effect, and Critical Behavior of Room Temperature Magnetic Refrigerant Material Mn5Ge2.7Zn0.3 - XU Tongjie, LIU Zhenhua, JIN Huaiyu, LIU Jie, JIANG Xiuli, LI Zhe, LIU Yongsheng (Shanghai Jiaotong Daxue xuebao)
Mn5Ge2.7Zn0.3 alloy was successfully prepared by using the arc-melting method, and its phase transition, magnetocaloric effect, and critical behavior were studied. The thermomagnetic curve determined that the Curie temperature of the sample was 297.2 K, the isothermal magnetization curve found that the sample had no thermal hysteresis. The sample underwent a second-order phase transition through the M2-H/M plot and Banerjee’s criterion, and the isothermal entropy change of the sample was further calculated according to Maxwell’s equation, and the power-law relationship of field-entropy and the normalization curve also verified the fact of the second-order phase transition. The critical index was solved by the modified Arrott plot(MAP) method, the Kouvel-Fisher(KF) method and the critical isothermal (CI) method, and the accuracy of the critical index was verified by Widom scaling ansatz and scaling laws. Finally, the Arrott-Noaks equation was used to further analyze the critical behavior of the sample, and the normalization slope and magnetic interaction distance were analyzed to confirm the complexity of the magnetic interaction inside the sample.